4/10
6/15
18/45
8/20
16/40
7 plus the sum of a number x and 5 write this phrase as an expression
The equation is: 7 + (x + 5)
The expression for '7 plus the sum of a number x and 5' is written as '7 + (x + 5)'.
The phrase '7 plus the sum of a number x and 5' can be written as an algebraic expression. This involves taking the sum of the variable x and the number 5, and then adding 7 to this sum. In mathematical terms, this is expressed as 7 + (x + 5).
Let's break it down step by step:
First, identify the sum: x + 5.
Next, add 7 to the result of this sum.
So, if we were to evaluate this expression for x = 4, we would calculate it as follows:
7 + (4 + 5) = 7 + 9 = 16
6a−3b=5b solve for a:b ratio plz help
The expression 6a − 3b = 5b after solving for a:b is 4:3 after using arithmetic operation.
What is the ratio?It is described as the comparison of two quantities to determine how many times one obtains the other. The proportion can be expressed as a fraction or as a sign: between two integers.
It is given that:
The expression is:
6a − 3b = 5b
To solve the above expression:
6a = 5b + 3b
6a = 8b
a/b = 8/6
As we know,
The expression can be defined as the combination of constants and variables with mathematical operators.
a:b = 8: 6
a:b = 4: 3
If in the linear expression, one variable is present, then the expression is known as the linear expression in one variabe.
Thus, the expression 6a − 3b = 5b after solving for a:b is 4:3 after using arithmetic operation.
Learn more about the ratio here:
brainly.com/question/13419413
#SPJ2
What is y= -1/3x-9 written in standard form
Simplify 1/3x to x/3
y = -x/3 - 9
Add 9 to both sides
y + 9 = -x/3
Multiply both sides by 3
(y + 9) * = -x
Regroup terms
3(y + 9) = -x
Using the formula, rewrite in standard form
Answer: x + 3y = -27
To convert the equation y = -1/3x - 9 to standard form, you need to eliminate the fraction and rearrange the equation. Multiply both sides of the equation by 3 to get 3y = -x - 27. Rearrange the equation to get x + 3y = -27, which is the standard form.
Explanation:The equation y = -1/3x - 9 can be written in standard form as Ax + By = C, where A, B, and C are constants. To write the equation in standard form, we need to eliminate the fraction by multiplying both sides of the equation by 3. This gives us 3y = -x - 27. Rearranging the equation, we get x + 3y = -27, which is the standard form.
Learn more about Converting equations to standard form here:https://brainly.com/question/30381343
#SPJ2
-15h + 100 = 40, but what is the value of k?
I don't know if you accidentally put down the wrong variable, but the answer for h would be h=4. First things first, you have to subtract 100 from both sides, and this would become -15h=-60. After that, divide -15 on both sides, thus it leaves you with h by itself and it's value is 4. h=4
Hope this was helpful:)
What is the antiderivative of e^x^2?
Answer: The antiderivative of [tex]e^{x^{2}}[/tex] is [tex]\sqrt{\pi} \sqrt{e^{x^2}-1} +C[/tex].
Explanation:
[tex]I=\int{e^{x^2}dx}\\I^2=\int{e^{x^2}dx}\int{e^{x^2}dx}[/tex]
Using dawson integral.
[tex]I^2=\int{e^{x^2}dx}\int{e^{y^2}dy}[/tex]
[tex]I^2=\int{\int{e^{x^2+y^2}dxdy}}[/tex]
Put [tex]x^2+y^2=r^2[/tex]
[tex]I^2=\int{\int{e^{r^2}rdrd\theta}}[/tex]
[tex]\int_{0}^{2\pi}{d\theta}\int_{0}^{x}{re^{r^2}dr}[/tex]
Use substitution method and sunbstitute [tex]r^2=t[/tex].
[tex]\int_{0}^{2\pi}{d\theta}\int_{0}^{x^2}{\frac{1}{2}e^tdt}[/tex]
[tex]I^2=\frac{1}{2}|\theta|_{0}^{2\pi}|e^t|_{0}^{x^2}\\I^2=\frac{1}{2}(2\pi)(e^{x^2}-1)\\I=\sqrt{\pi}\sqrt{e^{x^2}-1}[/tex].
Therefore, the antiderivative of [tex]e^{x^{2}}[/tex] is [tex]\sqrt{\pi} \sqrt{e^{x^2}-1} +C[/tex].
Billy has $18.36. he bought turtle and cat treats. how much money did he have left?
it depends on how much the turtle and the dog treats are use that like 5 dolor each so im going to say 8 maybe
pls help me i need help asap
its's 200 sq feet, I added extra lenghts and the circled numbers are areas for that part of the shape.
What is the greatest number of 18 and 9
greatest number for what
Round 395.9 to the nearest whole number
396 is the answer since it's closer to the 10's than the 0s
an above ground swimming pool is leaking. after 1/2 hour the pool has leaked 7/8 of a gallon of water. how many more gallons of water per hour is the swimming pool leaking?
The swimming pool is leaking 1 6/8 gallons of water per hour.
Answer:
1.75 gallons/hour
Step-by-step explanation:
Thinking process:
The leaking amount in a half hour = [tex]\frac{7}{8}[/tex]
The amount of water that leaks per hour = [tex]2 * \frac{7}{8} \\= \frac{7}{4}\\ = 1.75 gallons/hour[/tex]
How do I calculate the volume of this pyramid?
V = 1/3 area of base * height
Area of base = h [(b₁ +b₂)]/2
[(3 + 6) * 4] : 2 =
18 ft²
Volume =
18 * 3 =
54 ft³
Does the function have a constant rate of change?
tickets to a movie cost $7.25 for adults and $5.50 for students. A group of friends purchased 8 tickets for $52.75. Determine the total number of adult and student tickets
Answer:
5 adult and 3 student tickets were purchased
Explanation:
Let x be the number of adult tickets
Then 8−x is the number of student tickets
7.25x+5.5(8−x)=52.75
7.25x+44−5.5x=52.75
1.75x=8.75
x=5
Therefore, 5 adult and 3 student tickets were purchased.
unit 15subtract fraction 1/3 - 1/6
Answer:
1/6
Step-by-step explanation:
First, you want the denominators to be the same so you can subtract them.
1/3=2/6
2/6-1/6=1/6
Hope this helped!
What substitution should be used to rewrite 4x^4-21x^2+20=0 as a quadratic equation
let y = x^2
4y^2 -21y + 20 = 0
solve for y
then substitute back in to get x
Answer:
4y^2 - 21y + 20 = 0
Step-by-step explanation:
As (4x^4 - 21x^2 + 20=0) being a biquadratic equation, meaning it is a 4-degree equation without the terms of degree 1 and 3.
To solve this particular case you only need to replace the variables of degree 4 and 2 for a new variable of degree 2 and 1 and solve it as regular quadratic equation and then undo the change.
* Using a new variable we can rewrite the equation:
Let y be the new variable;
y= x^2, then y^2= x^4
Then we have;
4y^2- 21y+20=0
Solve for y and then find X which will be the roots for the biquadratic equation.
The distance from the earth to the sun is 9.3×10 to the 6(power) miles. The distance from earth the moon is 3×10 to the 5th(power) miles. How many times bigger is the distance from earth to the sun than the distance from earth to the moon?
Answer:
NO the Earth to Sun distance is 9.3 x 10^7 miles.
Earth to Noon distance is 2.4 x 10^5 miles
9.3 x 10^7 is 387.5 times larger than 2.4 x 10 ^ 5
Step-by-step explanation:
Answer:
31 times bigger is the distance from earth to the sun than the distance from earth to the moon.
Step-by-step explanation:
Given : The distance from the earth to the sun is 9.3×10 to the 6(power) miles. The distance from earth the moon is 3×10 to the 5th(power) miles.
To find : How many times bigger is the distance from earth to the sun than the distance from earth to the moon?
Solution :
The distance from the earth to the sun is [tex]9.3\times 10^{6}[/tex] miles.
The distance from the earth to the moon is [tex]3\times 10^{5}[/tex] miles.
To know, times bigger is the distance from earth to the sun than the distance from earth to the moon is given by,
[tex]n=\frac{9.3\times 10^{6}}{3\times 10^{5}}[/tex]
[tex]n=3.1\times 10^{6-5}[/tex]
[tex]n=3.1\times 10[/tex]
[tex]n=31[/tex]
Therefore, 31 times bigger is the distance from earth to the sun than the distance from earth to the moon.
Solve the inequality 1 ≤ s -8
1 ≤ s -8
1+8 ≤ s
9. ≤ s
The value of the variable s is greater than or equal to 9.
What is inequality?Inequality is defined as an equation that does not contain an equal sign. Inequality is a term that describes a statement's relative size and can be used to compare these two claims.
Making anything easier to accomplish or comprehend, as well as making it less difficult, is the definition of simplification.
The inequality is given below.
1 ≤ s - 8
Simplify the inequality, then the value of the variable s will be
1 ≤ s - 8
1 + 8 ≤ s
9 ≤ s
Thus, the value of the variable s is greater than or equal to 9.
More about the inequality link is given below.
https://brainly.com/question/19491153
#SPJ2
Find -7 -(-3)=
What’s the answer explain !
Because there are 2 minus signs next to each other, we can replace both of them with a single plus sign.
This changes the equation to -7 + 3
Adding to a negative number makes the number appear smaller, so 3 + -7 = -4.
Remove parenthesis
-7=3
Calculate the sum
-4
An airplane is traveling at a speed of 200 km/h. Compute the speed of the airplane in m/s.
A) 3.3 m/s
B) 33.3 m/s
C) 55.6 m/s
D) 111.20 m/s
Given the speed is 200 km /hr
use 1 km = 1000 meter
1 hr = 3600 seconds
so
[tex]200 km/hr = \frac{200*1000}{1*3600} m/s[/tex]
simplifies to
[tex]\frac{5000}{9} m/s[/tex]
[tex]55.6 m/s[/tex]
so option C
Answer: C) 55.6 m/s
Step-by-step explanation: 200km/1hr x 1000m/1km x 1hr/60min x 1min/60s = 55.6 m/s
If the conversion factors are properly set up and all numbers are correct, the unwanted units cancel out leaving the units of the final answer.
A line segment is drawn between the points (5,8) and (-1,6). What are the coordinates of the midpoint of the segment?
The formula of a midpoint between two points:
[tex]M\left(\dfrac{x_1+x_2}{2},\ \dfrac{y_1+y_2}{2}\right)[/tex]
We have (5, 8) and (-1, 6).
Substitute:
[tex]\dfrac{5+(-1)}{2}=\dfrac{4}{2}=2\\\\\dfrac{8+6}{2}=\dfrac{14}{2}=7[/tex]
Answer: The coordinates of the midpoint of the segment are (2, 7).
Solve for this equation 80=3y+2y+4+1
80 = 3y + 2y + 4 +1
80 = 5y + 5
80 - 5 = 5y
75 = 5y
75 = 5y/5y
75/5 = y
15 = y
2cosx-1=.0068 find x in degrees
Answer:
60 degree
Step-by-step explanation:
adding 1 both sides of equation
2cos x -1+1 = 0.0068 +1
2cosx = 0.9932
dividing by 2 both sides
cosx = 0.9932 / 2
cosx =0.4966
x= cos^-1(0.4966)
x=60 degree
The graph of the distance a car travels at a constant speed passes through the points (0,0) and 2,136). The x scale is hours and the y scale is miles. How fast is the car traveling?
A. 134 miles per hour
B. 68 miles per hour
C. 34 miles per hour
D. 136 miles per hour
We are given that
y-scale is a distance in miles
x-scale is a time in hours
and we are given
The graph of the distance a car travels at a constant speed passes through the points (0,0) and (2,136)
so, points would be
(0,0)
x1=0 , y2=0
(2,136)
x2=2 , y2=136
so, slope would be speed
because speed = distance / time
we can use slope formula
[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]
now, we can plug values
[tex]m=\frac{136-0}{2-0}[/tex]
[tex]m=68[/tex] miles per hour
so, option-B..........Answer
Answer:
B
Step-by-step explanation:
triangle ABC is similar to triangle PQR , As shown below :
which equation is correct ?
(DONT ANSWER IS UR NOT SURE )
Answer:
Option C is correct
Step-by-step explanation:
In similar triangles corresponding sides are in same ratio.
Notice that sides b and q are corresponding ( they are opposite equal angles) and so are a and p
The correct equation from the option is b/q = a/p. Hence, option C is correct.
How to express similar sides as a proportionTo make a proportional relationship from the two triangles ABC and PQR given ;
Express corresponding sides as ratios ;
a/pb/q c/rUsing the given sides , the possible proportions are ;
a/p = b/q
b/q = c/r
a/p = c/r
Comparing the ratios with the options given, Only option B gives a correct proportional relationship.
Learn more on similar triangles : https://brainly.com/question/32325828
#SPJ3
Divide 28x3 + 42x2 − 35x by 7x
(28x^3 + 42x^2 - 35x) / 7x
** keep in mind, when dividing exponents, u subtract the exponents
4x^2 + 6x - 5 <==
mark brainliest plsss
Answer:
[tex]4x^{2} +6x -5[/tex].
Step-by-step explanation:
Given : 28x³ + 42x² − 35x .
To find : Divide by 7x .
Solution : We have given 28x³ + 42x² − 35x .
Divide by 7x
28x³ + 42x² − 35x ÷ 7x.
Now Distribute 7x over 28x³ + 42x² − 35x to divide the terms.
[tex]\frac{28x^{3}}{7x} +\frac{42x^{2} }{7x} -\frac{35x}{7x}[/tex].
[tex]4x^{2} +6x -5[/tex].
Note : on dividing exponent is subtract.
Therefore, [tex]4x^{2} +6x -5[/tex].
Factor the expression. k2 + 5kf – 50f2
Answer:
We have
k^2 - 25f^2 + 5kf - 25f^2 =
k^2 - (5f)^2 + 5f( k - 5f) =
( k - 5f )( k + 5f ) + 5f( k - 5f ) =
( k - 5f )( k + 5f + 5f ) =
( k - 5f )( k + 10f );
Step-by-step explanation:
Answer: The required factored form of the given expression is [tex](k-5f)(k+10f).[/tex]
Step-by-step explanation: We are given to factor the following quadratic expression :
[tex]E=k^2+5kf-50f^2~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To factor the given expression, we need two integers with sum 5 and product -50 and those two integers are 10 and -5.
The factorization of expression (i) is as follows :
[tex]E\\\\=k^2+5kf-50f^2\\\\=k^2+10kf-5kf-50f^2\\\\=k(k+10f)-5f(k+10f)\\\\=(k-5f)(k+10f).[/tex]
Thus, the required factored form of the given expression is [tex](k-5f)(k+10f).[/tex]
Square root of 3^4 or √3^4
A.1
B.2
C.3
D.4
Answer:
answer is 9.
Step-by-step explanation:
can someone write me a original geometry poem? (just a short poem about geometry or geometric shapes!) thanks in advance!
how many solutions does 5x+6=2x+6+3x-15 have
*(Step-By-Step)*
[tex]5x+6=5x-9[/tex] Combine Like Terms
[tex]6=9[/tex] Subtract [tex]5x[/tex] to both sides
*(Answer)*= No solution because [tex]6[/tex] is not [tex]9[/tex]
Hope this helps
BangtanBoyScouts
GIVING AWAY 35 POINTS! What is the graph of this function?
Answer:
Im pretty sure its graph A
Step-by-step explanation:
Answer:
graph A
Step-by-step explanation: